Acrylamide content in selected food products collected from Montenegrin market and health risk assessment - Đurović, Dijana; Bigović, Miljan; Ivanović, Ljubica; Blagojević, Maja; Orahovac, Amil (Central European journal of public health, 2024)
OBJECTIVES: This study aimed to investigate the acrylamide exposure of different children and adult population groups (10-14 years, 15-17 years, 18-24 years, 25-44 years, 45-64 years, and 65-74 years) resulting from the consumption of potato chips and wheat-based bread from Montenegrin market and to evaluate it in terms of health risk. METHODS: The acrylamide content was monitored in 51 samples of bread and 20 samples of chips. The carcinogenic health risk in different population groups was assessed through the incremental lifetime cancer risk (CR) and total cancer risk (TCR). RESULTS: The average acrylamide content in potato chips and bread was calculated to be 238 μg/kg and 30 μg/kg, respectively. Acrylamide content in a tested sample met the criteria prescribed by Commission Regulation (EU) 2017/2158 in 98% of the tested samples of chips and 85% of bread samples. The carcinogenic health risk of acrylamide exposure for the investigated population groups is of concern. The values of CR for all the investigated groups were in the range of 10-6 < CR < 10-4 and the values of TCR were 10-5 order of magnitude, indicating a potential cancer risk. CONCLUSION: The youngest population (10-14 years) was exposed to the highest cancer risk through the consumption of both, chips and bread. For the population of 10-14 years, 15-17 years, 25-44 years, 45-64 years, and 65-74 years, a higher risk of cancer was found due to the consumption of bread compared to the consumption of chips. Only the population aged 18-24 years was faced with a higher risk of cancer due to the consumption of chips compared to the consumption of bread.
Keywords: dospělí; Solanum tuberosum; hodnocení rizik; Female; dítě; Adult; ženské pohlaví; mladý dospělý; Food Contamination; Neoplasms; nádory; Adolescent; Food Analysis; chléb; lidé; Acrylamide; Risk Assessment; akrylamid; kontaminace potravin; analýza potravin; Male; Aged; Young Adult; lidé středního věku; Černá Hora; Child; senioři; mužské pohlaví; Middle Aged; mladiství; Montenegro; Bread; Humans